Water strains of Leptospira in the serodiagnosis of human and animal leptospirosis - Addamiano, L. (1968)
The most widely used serological reaction for the diagnosis of leptospirosis is the agglutination test. This test, however, cannot be carried out in many laboratories because special equipment and special experience are required. It is also necessary to maintain live Leptospira cultures belonging to all the serotypes present in the country where the test is made. Consequently, it would be extremely useful to be able to diagnose leptospirosis by means of a single antigen, regardless of the serotype to which the Leptospira responsible for the infection belonged. This is particularly important for countries in which the antigenic pattern of the local leptospirae is not well known and in which it would thus be necessary to use a large number of Leptospira serotypes for each test. Observations made in the last 11 years have suggested that the problem may be solved with the use of some non-pathogenic, water strains of Leptospira which seem to be agglutinated by human sera containing antibodies against pathogenic leptospirae. This paper reports the results of studies from 1960 to 1968 on the possibility of using water strains for serodiagnosis. The results over the 8-year period show that the non-pathogenic strain Patoc 1 is agglutinated by a high percentage of human sera positive for pathogenic leptospirae: these results indicate that Patoc 1 would be useful for serodiagnosis. However, a high percentage of animal sera positive for pathogenic leptospirae gave negative results with the strains Patoc 1 and Sao Paulo, and thus these strains cannot be used for serodiagnosis in animals.